2007
DOI: 10.1093/annonc/mdm007
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies in breast cancer: their use as an aid to early diagnosis

Abstract: Autoantibodies against one or more of these tumour-associated antigens appears to indicate the presence of early-stage breast cancers. Autoantibody assays against a panel of antigens could be used as an aid to mammography in the detection and diagnosis of early primary breast cancer, especially in younger women at increased risk of breast cancer where mammography is known to have reduced sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
224
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(233 citation statements)
references
References 13 publications
7
224
2
Order By: Relevance
“…Response rates to single antigens in this population ranged from 3% to 34%, but response rates for healthy controls were not reported. 50 Although preliminary, these data support further investigation to develop a multiplexed serum antibody based assays for breast cancer diagnosis.…”
Section: Detecting Serum Antibody Response To a Panel Of Taasmentioning
confidence: 60%
“…Response rates to single antigens in this population ranged from 3% to 34%, but response rates for healthy controls were not reported. 50 Although preliminary, these data support further investigation to develop a multiplexed serum antibody based assays for breast cancer diagnosis.…”
Section: Detecting Serum Antibody Response To a Panel Of Taasmentioning
confidence: 60%
“…Similar publications on other single autoantibodies (39-41) also indicate the induction of autoantibodies happening relatively early in the process of carcinogenesis. Autoantibodies to a panel of cancer-associated antigetns have been reported up (32) in lung cancer and up to 4 years before screening mammography detected breast cancers in young women at increased risk (31,33). A recent presentation on SCLC has shown that EarlyCDT-Lung was positive in prediagnostic samples between 1 and 49 months prior to diagnosis of SCLC (42).…”
Section: Discussionmentioning
confidence: 99%
“…Self-proteins (autoantigens) altered before or during tumor formation can elicit an immune response (13)(14)(15)(16)(17)(18)(19). These tumor-specific autoantibodies can be detected at early cancer stages and prior to cancer diagnosis revealing a great potential as biomarkers (14,15,20). Tumor proteins can be affected by specific point mutations, misfolding, overexpression, aberrant glycosylation, truncation, or aberrant degradation (e.g.…”
Section: Colorectal Cancer (Crc)mentioning
confidence: 99%